Traumatic Brain Injury: Ultrastructural Features in Neuronal Ferroptosis, Glial Cell Activation and Polarization, and Blood–Brain Barrier Breakdown - Delong Qin; Junmin Wang; Anh Le; Tom J. Wang; Xuemei Chen; Jian Wang (Cells, 2021)
The secondary injury process after traumatic brain injury (TBI) results in motor dysfunction, cognitive and emotional impairment, and poor outcomes. These injury cascades include excitotoxic injury, mitochondrial dysfunction, oxidative stress, ion imbalance, inflammation, and increased vascular permeability. Electron microscopy is an irreplaceable tool to understand the complex pathogenesis of TBI as the secondary injury is usually accompanied by a series of pathologic changes at the ultra-micro level of the brain cells. These changes include the ultrastructural changes in different parts of the neurons (cell body, axon, and synapses), glial cells, and blood–brain barrier, etc. In view of the current difficulties in the treatment of TBI, identifying the changes in subcellular structures can help us better understand the complex pathologic cascade reactions after TBI and improve clinical diagnosis and treatment. The purpose of this review is to summarize and discuss the ultrastructural changes related to neurons (e.g., condensed mitochondrial membrane in ferroptosis), glial cells, and blood–brain barrier in the existing reports of TBI, to deepen the in-depth study of TBI pathomechanism, hoping to provide a future research direction of pathogenesis and treatment, with the ultimate aim of improving the prognosis of patients with TBI.